AKR1D1 and CYP7B1 mutations in patients with inborn errors of bile acid metabolism: Possibly underdiagnosed diseases - Ju-Yin Chen; Jia-Feng Wu; Akihiko Kimura; Hiroshi Nittono; Bang-Yu Liou; Chee-Seng Lee; Ho-Sheng Chen; Yu-Chun Chiu; Yen-Hsuan Ni; Steven Shinn-Forng Peng; Wang-Tso Lee; I-Jung Tsai; et al. (Pediatrics and Neonatology, 2020)
Background: Inborn errors of bile acid metabolism (IEBAM) cause rare but treatable genetic disorders that can present as neonatal cholestasis or neurological diseases. Without timely primary bile acid treatment, patients may develop liver failure early in life. This study aimed to analyze the types and treatment outcomes of IEBAM in Taiwanese infants and document the allele frequency of CYP7B1 hot spot mutations in the population. Methods: Urine samples from patients with infantile intrahepatic cholestasis and suspected IEBAM were subjected to urinary bile acid analysis by gas chromatography-mass spectrometry (GC/MS). Genetic diagnoses were made using direct sequencing or next-generation sequencing. We also tested healthy control subjects for a probable hot spot point mutation of CYP7B1. Results: Among the 75 patients with infantile intrahepatic cholestasis tested during 2000 –2016, three had ∆4-3-oxosteroid 5β-reductase deficiency with AKR1D1 mutations, and three had oxysterol-7α-hydroxylase deficiency with CYP7B1 mutation. Two patients with ∆4-3-oxosteroid 5β-reductase deficiency were successfully treated with cholic acid. The three unrelated infants with oxysterol 7α-hydroxylase deficiencies had the same p.R112X homozygous CYP7B1 mutation. Two had mild renal or neurological involvement. Among 608 healthy control subjects, the allele frequency of the heterozygous mutation for p.R112X was 2/1216 (0.16%). The only surviving patient with oxysterol 7α-hydroxylase deficiency recovered from liver failure after chenodeoxycholic acid (CDCA) treatment beginning at 3 months of age. Conclusion: Distinct types of IEBAM disease were found in the Taiwanese population. Patients with early diagnosis and early treatment had a favorable outcome. IEBAM prevalence rates may be higher than expected due to the presence of heterozygous mutations in the general population. Key Words: chenodeoxycholic acid, cholic acid, inborn errors of bile acid metabolism, neonatal cholestasis, oxysterol 7α-hydroxylase deficiency